A Manifesto for project management research. Issue 1 (21st March 2023) - Locatelli, Giorgio; Ika, Lavagnon; Drouin, Nathalie; Müller, Ralf; Huemann, Martina; Söderlund, Jonas; Geraldi, Joana; Clegg, Stewart
Abstract: Project management research has evolved over the past five decades and is now a mature disciplinary field investigating phenomena of interest to academics, practitioners and policymakers. Studies of projects and project management practices are theoretically rich and scientifically rigorous. They are practically relevant and impactful when addressing the pursuit of operational, tactical and strategic advancements in the world of organisations. We want to broaden the conversation between project management scholars and other scholars from cognate disciplines, particularly business and management, in a true scholarship of integration and cross‐fertilisation. This Manifesto invites the latter scholars to join efforts providing a foundation for further creative, theoretical and empirical contributions, including but not limited to tackling grand challenges such as climate change, pandemics, and global poverty. To this end, we identify five theses: Projects are often 'agents of change' and hence fundamental to driving the innovation and change required to tackle grand challenges. Much project management research leverages and challenges theories across disciplines, including business, organisation and management studies, contributing to developing new theories, including those specific to projects and temporary organisations. 'Projects' are useful units of analysis, project management research is ideal for scientific cross‐fertilisation and project management scholars welcome academics from other communities to engage in fruitful conversations. As in many other fields of knowledge, the project management research community embraces diversity, welcoming researchers of different genders and various scientific and social backgrounds. Historically rooted in 'problem‐solving' and normative studies, project management research has become open to interpretative and emancipatory research, providing opportunities for other business, management and organisational scholars to advance their knowledge communities.